THE RELATIONSHIP OF DIGITAL LITERACY TO STUDENTS' COGNITIVE ABILITY IN ECOLOGY COURSE - Windy Marisa; Ely Djulia (Universitas Negeri Medan, 2022)
This correlation study aims to determine the relationship between digital literacy and students' cognitive abilities in ecology courses. The subjects of this study were students at the State University of Medan 2018 class of Biology Education who took ecology courses in the 2020/2021 academic year. There were 152 students, and samples were taken using the purposive sampling technique of 61 students. The data were processed with descriptive qualitative research, and the data collection techniques used in this research were a questionnaire. The results showed a relationship between digital literacy and students' cognitive abilities in ecology courses with r = 0.791, and digital literacy contributed (62.6%) to students' cognitive abilities in ecology courses. In conclusion, someone with good literacy will also have good cognitive abilities. The growth of technology for education will continue to develop increasingly over time so that digital literacy in the educational environment is beneficial for students in covering broader and deeper information and will help students to complete their assignments and find accurate information.